Sistem Pendukung Keputusan Penilaian Kinerja Guru dalam Kenaikan Gaji Menggunakan Metode SAW di SMK Muthia Harapan - Miki Wijana; Hani Mulyani (Jurnal Accounting Information System (AIMS), 2023)
Teacher performance assessment is an important component in efforts to improve the quality of education. The use of a Decision Support System (DSS) with a website-based Simple Additive Weighting (SAW) method with PHP and SQL allows the teacher performance assessment process to be more efficient and objective. This system integrates information from various sources, such as student data, exam result data, peer evaluations, and classroom observations. Muthia Harapan Vocational School is a vocational school with a private educational institution. Decision making for teacher salary increases is still manual or not yet computerized, which causes errors and not being on target. In this research, designing and developing a website that functions as a platform for assessing teacher performance. Teachers can enter their data and upload evidence of their performance. The system then performs calculations based on the weighting criteria determined by the school or educational institution. The SAW method is used to calculate teacher performance scores based on these criteria. It is hoped that the use of the Decision Support System using the website-based SAW method can increase objectivity in assessing teacher performance, enable more precise decision making, and contribute to improving the overall quality of education.